2017
DOI: 10.1177/0021998317710083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the characterization of voids in glass fiber composites

Abstract: Voids are a concern in composite materials, as they may have a negative effect on the mechanical properties of the laminates. Voids may develop especially in low cost or off-optimum process conditions. In this study, samples of glass reinforced epoxy laminates with void volume fractions in the 0.5–7% range were successfully obtained by varying the vacuum in the hand layup vacuum bagging manufacturing process. Void content was experimentally characterized using four different methods: ultrasonic scanning, epoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…This may be because the latter excludes the voids connected to the specimen's outer surface. The difference between void content measured via micro-CT and that measured via other techniques was also reported in [23][24][25][26].…”
Section: Introductionmentioning
confidence: 78%
“…This may be because the latter excludes the voids connected to the specimen's outer surface. The difference between void content measured via micro-CT and that measured via other techniques was also reported in [23][24][25][26].…”
Section: Introductionmentioning
confidence: 78%
“…With the same reasoning, the number of detected small voids increased with improving the resolution of micro-CT. However, for an NCF glass/epoxy composite, Abdelal and Donaldson 187 concluded that micro-CT could detect the high increase in void content with decrease in manufacturing vacuum, while the increase detected by “manual” tomography (explained in Void shape (morphology) section) and density determination techniques were less significant. They found the US technique incapable of identifying the voids in their case.…”
Section: Characterization Of Voidsmentioning
confidence: 98%
“…More recently, Straumit et al 187 used the structure tensor method to build a voxel model with the fiber orientation data extracted from micro-CT images (VoxTex software). Using the k-means clustering algorithm, they could segment the voxel models into yarns, matrix, and voids, which can be used in creating realistic models of the composite.…”
Section: Ultrasonic Testingmentioning
confidence: 99%
“…High resolution X-Ray Computed Tomography (CT-scan) visualizes the interior features within a solid object by obtaining digital images of the object geometry and the properties [1]. The CT technique is a non-destructive slicing technique depicting what the object being scanned would look like if it were sliced open along a plane.…”
Section: High Resolution X-ray Computed Tomography (Ct)mentioning
confidence: 99%
“…Advanced composites can be divided into laminates and sandwiches. The laminates are layers or plies of composite materials bonded together, whereas, the sandwich is a multiple-layer composite structure consisting of a low-density core between thin laminate faces (skins) of composite materials [1].…”
Section: Introductionmentioning
confidence: 99%